Effet de l'enveloppe séminale de la graine d'arachide sur les moisissures pathogènes de germination - Lumpungu, K.; Baelenge, B.; Bitijula, M. (Tropicultura, 1989)
Effect of seminal envelope of groundnut seed on fungi pathogenic to germination. The effect of seminal envelope of groundnut seed on the development of pathogenic fungi has been studied in lab conditions. The results have shown that the seeds devoided of seminal envelopes and no soaked in distilled water or in Mg and minor elements solution have been greatly attaqued by pathogenic mildew. In the same way, KMn04 and "testas" extracts treatment have inhibited the development of the pathogenic fungi.